3 in 1 processor coconut dehusker machine - Ngadiron, Mohamad Faridzuan; Mohd Noor, Mohamad Ashraffudin; Hassan, Mohd Fahrul; Mohammad, Nur Adela; Shah Hamid, Saidatul Nabilah; Abd Rahim, Muhammad Syafiq (Penerbit UTHM, 2017)
The main coconut machine consists of five main processes that is dehusking process, grating and extracting process. Our group needs to focus only on the husking process machine. This machine needs to consider that it can operate fully automatic in indoor environment and produces less sound. In general, coconuts are dehusked manually using either a machete or a spike. These methods require skilled labor and are tiring to use. attempts made so far in the development of dehusking tools have been only partially successful and not effective in replacing manual methods. Considering the drawbacks of manual dehusking methods, and existing automated dehusker, power operated coconut dehusking machine was developed. This coconut dehusking machine peels off the coconut husk from coconut fruit to obtain dehusked coconut fruit as shown in figure 3.1.